2021
DOI: 10.1111/codi.15839
|View full text |Cite
|
Sign up to set email alerts
|

Ileorectal anastomosis in patients with Crohn’s disease. Postoperative complications and functional outcome—a systematic review

Abstract: Aim The objective of this systematic review was to investigate the outcomes of ileorectal anastomosis (IRA) in Crohn’s disease and to clarify whether there are any time‐related trends in outcome measures. The primary outcomes are risk of anastomotic leakage, death, clinical recurrence and subsequent diverting or permanent stoma and/or proctectomy. Secondary end‐points are quality of life and functional outcome. Methods Systematic searches were conducted using the Cochrane Library, Embase and MEDLINE. The compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…12,13 Although indication for surgery due to clinical treatment failure has decreased in the past 60 years, a recent meta-analysis found that it still remains high: 47% 5 years after diagnosis. 14,15 Patients who are intolerant to or with poor adherence to clinical treatment, with corticosteroid dependency, refractory to drug treatment, or with primary or secondary treatment failure may benefit from surgical treatment. 14 Patients with colonic CD have a 2-3 times greater risk of colorectal cancer, for which the risk factors include: extensive disease, disease duration, family risk of colorectal cancer, and primary sclerosing cholangitis.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Although indication for surgery due to clinical treatment failure has decreased in the past 60 years, a recent meta-analysis found that it still remains high: 47% 5 years after diagnosis. 14,15 Patients who are intolerant to or with poor adherence to clinical treatment, with corticosteroid dependency, refractory to drug treatment, or with primary or secondary treatment failure may benefit from surgical treatment. 14 Patients with colonic CD have a 2-3 times greater risk of colorectal cancer, for which the risk factors include: extensive disease, disease duration, family risk of colorectal cancer, and primary sclerosing cholangitis.…”
Section: Discussionmentioning
confidence: 99%
“…The present study has results that are consistent with the current body of evidence for TCIRA as a treatment for constipation. Individual studies may present varying results; however, the overall picture is that of patient satisfaction with surgery despite heterogeneous functional outcomes with frequent continuation of pain and bloating symptoms and the possibility for very poor functional outcomes [5‐10,16,17,19,22‐27].…”
Section: Discussionmentioning
confidence: 99%
“…Individual studies may present varying results; however, the overall picture is that of patient satisfaction with surgery despite heterogeneous functional outcomes with frequent continuation of pain and bloating symptoms and the possibility for very poor functional outcomes [5][6][7][8][9][10]16,17,19,[22][23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review published in 2021 that included 37 studies assessing the outcome of ileorectal anastomosis in Crohn's disease found a cumulative anastomotic leak rate of 6.4%, cumulative rates of clinical recurrence of 43% at 5 years and 67% at 10 years, and an overall rate of proctectomy of 18.9%. 65 The authors also reported only minor improvements in outcomes for ileorectal anastomosis in the setting of Crohn's disease over the past 50 years, in spite of the advances in the medical management of Crohn's disease over this time frame.…”
Section: Ileorectal Anastomosismentioning
confidence: 99%